Гиблое дело: [роман] / Павел Савинов - Савинов Павел Николаевич (Черная метка, 2001)
Экземпляры: ф.2 (2002) / Инвентарный номер: 43945 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: С 13 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44